EVALUATION OF COGNITIVE, PSYCHOMOTOR, AND AFFECTIVE ASPECTS IN THE SUBJECT OF ISLAMIC EDUCATION - Bahari, Jon Iskandar (INCARE, International Journal of Educational Resources, 2023)
Based on the results of the observations that the researchers did, indirectly the PAI subject teachers had implemented evaluations of cognitive, psychomotor and affective aspects, but the majority of students had not reached the assessment indicators, namely in the cognitive, psychomotor and affective domains. In the cognitive evaluation, the majority of students had difficulty understanding the lesson so that the scores of students' written tests and oral tests did not reach the assessment indicators. In the psychomotor evaluation, students found it difficult to practice the material presented by the teacher, namely in performance assignments, projects and portfolios. In evaluating the affective aspects of the learning process, students pay less attention when the teacher explains the material, outside of school hours students have not been able to practice the material and the various attitudes of students. Describe how the evaluation of affective aspects of learning is carried out in the subject of Islamic Religious Education (PAI) class VIII C at SMPN 1 Tegalsari Banyuwangi, How are the results of the Learning Evaluation of Cognitive Psychomotor and Affective Aspects in the subject of Islamic Religious Education (PAI) class VIII C at SMPN 1 Tegalsari Banyuwangi, and How is the Impact of Learning Evaluation on Psychomotor and Affective Cognitive Aspects in Islamic Religious Education (PAI) class VIII C subjects at SMPN 1 Tegalsari Banyuwangi. This study uses a qualitative method with a case study approach, the authors conduct research with a descriptive analysis study, because it is in accordance with the nature of the problem and the research objectives to be obtained by the researcher, the researcher's data collection techniques use direct observation, semi-structured interviews and documentation then the researcher analyzes the the answer is done by collecting data, reducing, displaying data, andconclusion drawing/ vertivacation. In the results of the presentation of the data obtained by researchers at Tegalsari 1 Public Middle School, it is clear that in the cognitive aspect the teacher uses written tests and oral tests. In the psychomotor aspect, the teacher uses performance, project and portfolio assessments. And in the affective aspect the teacher assesses students' attitudes using observation and journals. What are the results of the evaluation of the cognitive, psychomotor and affective aspects of learning. The results of the evaluation of the cognitive aspect of learning are that there are students whose grades are above the KKM and below the KKM, the results of the evaluation of the psychomotor aspect are that the teacher can find out or measure the abilities of students' skills, while the results of the evaluation of the affective aspect of learning are that the teacher knows the attitudes of various students. In addition, there is an impact on the evaluation of cognitive, psychomotor and affective aspects of learning. The impact of evaluating the cognitive aspect is that students have broader insights, the impact of evaluating the psychomotor aspect is that students become creative and solutive, while the evaluation of the affective aspect has several impacts, namely the impact on students, teachers and schools.